The Wave of Student Unrest and Implications for the Secondary-School Counselor - Ashby, Sister M. Aloysius (Canadian Journal of Counselling and Psychotherapy, 2012)
In this article the writer states that student unrest is not peculiar to the present century, but that the changed conditions of modern life and the rapid increase in population have given it a new dynamic form. There is great hope for mutual understanding between age and youth; the emergence of counseling as a profession and the continued dependence of youth on their elders are the two avenues to happy collabora- tion.The current problems of drug addiction, sex and loss of faith are considered and there are references for those who would read more on these topics. The importance of group counseling and group activities is stressed but these will not replace the need for individual counseling. It is the adult who must remove the inconsistencies from his life if he wants to earn and keep the confidence of the young.